Tourism and development in Southeast Asia: Concluding remarks and future outlook - Dolezal, Claudia; Trupp, Alexander *; Bui, Huong T. (Routledge, 2020)
This chapter offers concluding remarks on the contributions in this volume. It first creates a summary by highlighting some overarching themes that emerged in the discussion on tourism and development in Southeast Asia. These include aspects such as community participation, livelihood diversification, urban-rural relationships, the breaking down of binaries, and the underused potential for tourism in the region. It then discusses the future outlook for tourism when used as a development engine in Southeast Asia, including structural changes, changing markets, new types of tourism and destinations, the Sustainable Development Goals and alternative development.